DYNAMIC CHARACTERISTIC ANALYSIS AND DESIGN IMPROVEMENTS OF FIRE TRUCKS LUFFING SYSTEM - WU XiaoQiang; ZHANG ChunYou (Jixie qiangdu)
Luffing system is an important part of fire ladder trucks,and plays a decisive role on the working stability.Aiming at the existing problems of fire ladder trucks in luffing conditions,researched on the dynamic characteristics of the main balancing valve,and drew the conclusion that balancing valve is the main cause of hydraulic fluctuations in luffing process,based on this,used AMESim to optimize the design of the structure of the balancing valve,selected the appropriate size of the orifice diameter. The simulation results showed that the hydraulic fluctuations in the luffing system had been effectively improved after the optimization,and achieved the desired aims. The solution will be reference for similar applying.